Merging the Social Influence Theory and the Goal-Framing Theory to Understand Consumers’ Green Purchasing Behavior: Does the Level of Sensitivity to Climate Change Really Matter? - Yang, Xianchuan; Tseng, Yafen; Lee, Beyfen (Frontiers in Psychology, 2021)
This study explored the formation of consumers’ green purchasing behavior (GPB) and investigated the moderating effect of sensitivity to climate change to address this current knowledge gap. An integrated model merging the Social Influence Theory and the Goal-framing Theory was developed with the S-O-R paradigm. An empirical study was conducted, surveying 583 respondents and analyzing the questionnaire results using structural equation modeling. The results show that media, family, and peer influence can effectively activate the consumers’ goal frames. Hedonic and normative goals had significant positive influences on GPB, while gain goals had no significant effect. Sensitivity to climate change was found to significantly moderate social influence on GPB through the consumers’ goal frames. This research provided strong empirical support on understanding the relationship between social influence and GPB through three goal frames. In addition, the potential differences of the GPB formation process in two subgroups (high sensitivity to climate change and low sensitivity to climate change) are also investigated. The results of this study can help green practitioners develop more effective marketing strategies and incentives targeted to consumers with varying levels of environmental consciousness or sensitivity.